Mid- and low latitude effects on eastern South African rainfall over the Holocene. (1st February 2020) - Miller, Charlotte; Hahn, Annette; Liebrand, Diederik; Zabel, Matthias; Schefuß, Enno
Abstract: Climate variability and its forcings in eastern South Africa during the late Quaternary remain poorly understood with data suggesting temporal variability and spatial heterogeneity. To constrain the variability and the drivers of past climate, we explore vegetation (C3 /C4 ) and hydrological change using stable carbon and hydrogen isotopes of plant-waxes and X-ray fluorescence (XRF) analysis in marine core GeoB20610-2 offshore the Limpopo River. We find evidence for two climatic phases: an initial arid phase ( c . 7–3 cal kyr BP), followed by a wetter phase ( c . 3–0 cal kyr BP). To put our findings into a regional context, we investigate a latitudinal transect of sites along eastern South Africa and divide the region into three distinct hydro-climatic zones, with significantly different climate drivers. During the last c . 3 cal. ka BP, wet climatic conditions dominated the northern summer rainfall zone (SRZ) and the southern South African zone (SSAZ), whereas arid conditions prevailed in the central and eastern SRZ . In the northern SRZ the climate was driven by local insolation, where heightened insolation resulted in more precipitation. The aridity during the last c . 3 cal. ka BP in the central and eastern SRZ and the increased humidity in the SSAZ are attributed to an equatorward displacement of the southern hemisphere westerlies, the South African high-pressure cell and the South Indian Ocean Convergence Zone (SIOCZ). For the Holocene we find little evidence for an Indian Ocean SST control on climate. The results for the Limpopo River catchment region highlight the spatial heterogeneity of Holocene climate conditions in eastern South Africa and indicate significant latitudinal differences in climate drivers. Highlights: Plant-waxes & XRF in GeoB20610-2 constrain the variability and drivers of past climate in SE Africa. Two climatic phases are identified: an arid phase (7–3 cal kyr BP) and wetter phase (3–0 cal kyr BP). The region is divided into three distinct hydro-climatic zones, with different climate drivers.